Growth control of Zeolitic Imidazolate Frameworks derived sulfides with the coexistence of nanosheets and nanoflowers for high performance supercapacitor. (25th August 2022) - Zang, Xiaobei; Wang, Xuemeizi; Liang, Liheng; Li, Chao; Qi, Hao; Shao, Qingguo; Cai, Yinghui; Cao, Ning
Abstract: Metal organic frameworks can be used as precursors to design and construct nano materials with various structures Here, we use a bimetallic Zeolitic imidazolate frameworks structure as a precursor to adjust the morphology of the electrode material and enhance its performance. This bimetallic type ZIF structure increases the electrochemically active area, optimizes the electronic orbitals, changes the charge transfer paths, and modulates the electronic structure. Subsequently, ZnCo-ZIF precursor is vulcanized using thioacetamide as a sulfur source to obtain ZnCoS/0.2 M NH4 F (ZCS/AF0.2 ) by a solvothermal method. Since the pH of the solution has a strong influence on the formation of the ZIF material during the preparation of the ZnCo-ZIF precursor, the pH of the solution is adjusted by NH4 F to obtain the structure of nanosheets (2D) coexisting with nanoflowers (3D). ZCS/AF0.2 electrode achieves high specific capacitance of 3175.5 F g −1 at 1 A g −1, with good rate capability and cyclic stability. In addition, asymmetric supercapacitor devices using the ZCS/AF0.2 and active carbon as positive and negative electrodes are fabricated, delivering high energy density of 89.8 W h kg −1 at the power density of 1103.3 W kg −1 and 41.2 W h kg −1 at the power density of 21, 500 W kg −1 . Graphical abstract: Unlabelled Image Highlights: ZnCo-ZIF was used as a precursor for the synthesis of ZIF-derived sulfides. Morphological control of ZnCoS/AF nanomaterials as regulated by NH4F concentration. A unique electrode material with coexistence of nanoflowers and nanosheets Two devices connected in series can power an electronic clock for more than 3 h